Penerapan Strategi Team Quiz Berbasis Pendekatan Konstuktivisme Pada Materi Siklus Air Untuk Meningkatkan Konsentrasi Belajar Siswa - Haryanti, Pri; Destrinelli, Destrinelli; Pamela, Issaura Sherly (Peneliti.net, 2024)
This research aims to see whether a team quiz strategy based on a constructivist approach to water cycle material can increase student learning concentration. This research is classroom action research using interview, observation and documentation methods. The research was conducted in class V at SDN 95/1 Olak, with the subjects being teachers and students. This research is classroom action research. The results of the research show that there is an increase in concentration in students that occurs after implementing the team quiz strategy based on a constructivist approach.